GEOECOLOGICAL STATE OF THE QARNOB DESERT LANDSCAPES AND AFFECTING FACTORS THEM - Ochilov, Sanjar Zokirovich; Abbasov, Subkhon Burkhonovich (SCIENCE and SOCIETY, 2026)
The article analyzes the geo-ecological state of Karnabchul landscapes and the natural and anthropogenic factors influencing it. The study examined the climatic characteristics of the region, soil cover, flora, and the level of pasture use based on scientific sources. The impact of wind erosion, soil salinization, desertification processes, and anthropogenic pressure on landscape stability was also highlighted. The results indicate that the disruption of the geo-ecological balance in the Karnabchul region has intensified in recent years. Climate change and increased economic activity have been identified as the primary factors accelerating landscape degradation.
Keywords: Karnabchul; geo-ecology; landscape; desertification; soil salinization; pasture degradation; climate change; wind erosion; anthropogenic factors